2014
DOI: 10.15640/jssw.v2n2a16
|View full text |Cite
|
Sign up to set email alerts
|

Asylum Seekers’ Credibility Burden: Managing Trauma in the Asylum Process without Collective Support

Abstract: In cases of asylum, individual asylum seekers experience victimization and discrimination on the basis of a social identity, however, the process of seeking government protection from a host society is an individualized course of action. The U.S. asylum system provides the legal means for asylum seekers to apply for permanent residency status based on their ability to document valid claims of persecution. Qualitative interviews with individuals applying for asylum (n=14) reveal an underlying uncertainty based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This condition was selected because the participants had experienced the asylum application process from initial application to eventually being granted status. Here, Rider (2014) suggests that during the asylum process applicants cannot present it as a stressful event; therefore, those who have been successful in their claim may be more likely to share their experiences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This condition was selected because the participants had experienced the asylum application process from initial application to eventually being granted status. Here, Rider (2014) suggests that during the asylum process applicants cannot present it as a stressful event; therefore, those who have been successful in their claim may be more likely to share their experiences.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have found such services are useful in providing practical support (Cuthill, Siddiq Abdalla and Bashir 2013), but falter in their assistance with asylum claims (Liebling et al 2014). Other research has found that asylum seekers were averse to approaching support services due to distrust and the fear of adversely affecting their asylum claim (Rider 2014).…”
Section: How the Asylum Process Affects Stress And Copingmentioning
confidence: 99%